1998
DOI: 10.1038/sj.bmt.1701506
|View full text |Cite
|
Sign up to set email alerts
|

Veno-occlusive disease of the liver after allogeneic bone marrow transplantation in children with hematologic malignancies: incidence, onset time and risk factors

Abstract: One hundred and forty children with hematologic malignancies undergoing allogeneic BMT were reviewed in order to clarify the incidence, onset time, and risk factors for veno-occlusive disease (VOD) of the liver. Thirty-eight patients (27.1%) developed VOD diagnosed according to the Seattle clinical criteria. Seventeen patients developed VOD within 20 days of transplantation (early-onset) and in 21 patients developed after day 20 (late-onset) including eight patients with histological confirmation. Late-onset V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 19 publications
3
58
1
Order By: Relevance
“…It has been reported that poor hepatic function reserve may be a risk factor for hepatic VOD. 20,21 Our results might be relevant to this hypothesis, because fibrous change can result in poor functional reserve of the liver. On day 0, levels of t-PA were significantly higher in patients with VOD than without VOD in this study.…”
Section: Risk Factorsmentioning
confidence: 76%
“…It has been reported that poor hepatic function reserve may be a risk factor for hepatic VOD. 20,21 Our results might be relevant to this hypothesis, because fibrous change can result in poor functional reserve of the liver. On day 0, levels of t-PA were significantly higher in patients with VOD than without VOD in this study.…”
Section: Risk Factorsmentioning
confidence: 76%
“…This patient may have been at higher risk than others in the series because she had had two prior stem cell transplants and had abnormal liver studies pre-therapy, both of which have been described as risk factors for VOD in the transplant setting. 8,10,22 The other seven patients tolerated GO therapy well without significant hepatotoxicity or VOD.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The cause of hepatic VOD is not entirely clear but a number of risk factors have been reported. [3][4][5][6] While many cases of mild VOD resolve spontaneously without complications, moderate-to-severe VOD may result in significant morbidity or even mortality. The management of VOD is mainly supportive, including fluid restriction and diuretics to ameliorate fluid retention and cardio-respiratory support if necessary.…”
Section: Introductionmentioning
confidence: 99%